Perancangan Sistem Informasi Monitoring Pelanggaran Siswa Berbasis Web - Dzikri, Muhammad; Kurniadi, Denny (Universitas Islam Negeri Sumatera Utara, 2024)
Website-based student offense monitoring information system is a web designed with the aim of monitoring student offenses at SMKN 2 Padang Panjang. The purpose of this information system is to provide accurate, fast and more efficient and effective information about student offenses, and assist schools in taking appropriate action. In its development, this information system uses the PHP programming language, MySQL as a database, and the Laravel framework as a web development tool. The features in this information system are student profile data collection, teacher account registration, and management of student offenses by teachers and admins. With this information system, it is also expected to increase student discipline in carrying out the rules that have been set at school. Keywords: Information System, Monitoring, Violation, Student, Web, Laravel Framework